Transformational Style of Leader in Community-based Tourism (Study Case on Ranggon Hills Group, Gunung Sari Village) - Lidya, Febby; Sarwoprasodjo, Sarwititi; Hubeis, Musa (Sodality: Jurnal Sosiologi Pedesaan, 2021)
Proverty and digital divide were the main problems of forming tourism bussines in rural areas, whereas this tourism group had to be able to develop independently. The group leader became central figure in forming and organizing tourism group. The aim of this research was to learn how the role leader through transformational style perspective to (1) increase the capacity group of community-based tourism, (2) address the problem of poverty, and (3) overcome the problem of digital divide. Method used in this research was qualitative research method with 13 representative informants which were chosen purposively and conducting triangulation step through in-depth interview against leaders and members as well as analyzing the WhatsApp conversation toward group organizer. In this research, it was also carried out an activity observation of main leadership and executor as well as members when the work activity was ongoing. The research shows that there are 2 leaders, the main leader and the executive leader, who collaborated in developing tourism group based on community-based tourism. This research was done through transformational style perspective with 4 load aspects such as idealized influence, motivational inspiration, intellectual stimulation, and individual consideration in managing and developing both individual and organizational capacity in Gunung Sari Village, Pamijahan’s sub district, Bogor district area.